DEVELOPMENT OF PRIMARY EDUCATION: SUPPORT OF MODERN TECHNOLOGIES (American Journal of Pedagogical and Educational Research, 2023)
The article reveals the main aspects of innovative digital technologies in the process of updating primary education. It summarizes the ideas that methodological and problematic innovative processes in connection with the renewal and new content of primary education should be given priority to increasing the craving for knowledge of younger students, updating educational technologies, improving the quality of educational services.